Penerapan Nilai-Nilai Al-Qur’an dalam Pendidikan Islam: Tinjauan Literatur - Febby Erika; Abu Anwar; Nur Azmira (Universitas Negeri Makassar, 2026)
The purpose of this study is to discuss the concepts, models, practices, obstacles, and implementation of Quranic values in Islamic education at the elementary level. The approach used in this study was qualitative, using literature observation of scientific journal articles published within the last five years. Data collection was conducted through documentation studies, which were then analyzed using qualitative descriptive data analysis techniques through the stages of data editing, grouping themes, interpretation, and drawing conclusions. The results of this study demonstrate the application of Quranic values in elementary education through curriculum integration, school culture instillation, and educator role models. This has been proven to positively contribute to strengthening student character. However, its implementation still faces obstacles such as limited teacher competency, limited learning time, and a lack of synergy between schools and families. The results also emphasize the importance of a holistic and collaborative approach to the sustainable instillation of Quranic values in elementary education.